Strategic Management in Improving the Quality of Islamic Religious Education Learning - Fikri Rizkia Muhammad; Ujang Nurjaman; Ahmad Sukandar; Ahmad Khori; Leo Lestere (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2022)
This article analyses strategies to improve the quality of Islamic Religious Education learning. Descriptive analysis, which began with observation, interviews, and documentation, was used. Therefore, various types of data were collected related to the research problem. Data verification was conducted, and the data were interpreted to obtain answers. The results showed that the teacher's program was administrative preparation, innovative and varied methods using media, practice, memorization, deposit, and writing the Qur'an. The principal programs were performed with motivation, cooperation, assignments, and daily, weekly, monthly, and yearly review learning. Meanwhile, the evaluations focused not on essays and multiple choice questions but on open questions and attitude assessments. Supporting factors are the principal's policy, complete facilities and infrastructure, educators, high motivation, and internal and external inhibiting factors arising from the teachers and unbalanced facilities. Concerning the required efforts, teachers always participate in training activities and seminars, and the school continues to add a few facilities. In conclusion, the strategy for improving the quality of learning is based on teacher and school programs, student morals, and achievement.